Mystery train - Jarmusch, Jim, 1953-; Jarmusch, Jim, 1953-; Kudoh, Youki, 1971-; Nagase, Masatoshi, 1966-; Hawkins, Screamin’ Jay; Lee, Cinqué; Braschi, Nicoletta, 1960-; Bracco, Elizabeth; Strummer, Joe; Aviles, Rick, 1952-1995; Buscemi, Steve, 1957- (Jim Jarmusch collection, 1989)
Τρεις ιστορίες διαδραματίζονται σε ένα φθηνό ξενοδοχείο του Μέμφις, κατά τη διάρκεια ενός εικοσιτετραώρου.